Void handling using Geo-Opportunistic Routing in underwater wireless sensor networks. (November 2017) - Kanthimathi, N.; Dejey
Abstract: Underwater Wireless Sensor Networks (UWSNs) consist of a group of acoustic sensor nodes that report the sensed information to the sink nodes at the surface level. The factors like multipath fading, path loss, Doppler spread, limited battery power, and high mobility void region cause UWSNs to become spatially variable. In this paper, the idea of Geography-based Opportunistic Routing (GOR) is applied to advance the packet towards the destination and to handle the void problem. The proposed design is termed as Void Handling using Geo-Opportunistic Routing (VHGOR). In executing so, a heuristic algorithm comprising two metrics, namely OREPP and NCD for optimal forwarder selection is proposed. Additionally, a void handling mechanism is also proposed that handles void in two ways. Quick hull algorithm that makes a convex hull assists to identify whether the void is convex or concave. When the node approaches a convex void, reconstruction of convex hull helps to determine an alternative way to resume the greedy forwarding if the node has neighbors within its proximity. Failure of convex void handling during communication void makes VHGOR switch to concave void handling (or) recovery mode to recover the packet from local maximum node and to route the packet to the destination. At the end of simulation, the proposed VHGOR results considerably improve the network performance when compared with the existing solutions, both in sparse and very dense networks.